2016
DOI: 10.18805/ajdfr.v35i1.9252
|View full text |Cite
|
Sign up to set email alerts
|

Selection and characterization of potential probiotic <italic>Lactobacilli spp</italic> isolated from chicken feces may be used as a potent antibacterial agent

Abstract: Lactobacillus strains commonly used as probiotics which possess some properties such as resistance to gastric acidity and bile salts, production of antimicrobial compounds, the ability to modulate immune responses, and adhesion to gut tissues. This study aimed to isolate, identify, production and characterization of the probiotic strains. Total of 10 digestive tracts of chickens fed without antibiotics for presence of Lactobacillus spp was evaluated. All isolates were grown with different conditions like effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…As the isolates were found negative for endospore formation, they were subjected to motility test by inoculating them in a motility agar medium. All the isolates were identified as none motile as their growth was limited only to the stab line and no growth was present around the sides of the stab line [19]. The antimicrobial activity of the selected isolates was assessed through agar well diffusion method using Escherichia coli, Salmonella thyphimurium and Stephylococcus aureus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the isolates were found negative for endospore formation, they were subjected to motility test by inoculating them in a motility agar medium. All the isolates were identified as none motile as their growth was limited only to the stab line and no growth was present around the sides of the stab line [19]. The antimicrobial activity of the selected isolates was assessed through agar well diffusion method using Escherichia coli, Salmonella thyphimurium and Stephylococcus aureus.…”
Section: Discussionmentioning
confidence: 99%
“…During this experiment, no growth was observed at 6.5% NaCl concentration while at 4% NaCl concentration three isolates (LS1, LS2 and LS5) were able to grow. All the isolates were showing better growth at 2% and 3% NaCl concentrations [19]. All the selected isolates were also subjected to bile salt tolerance activity which is considered to be the most important selection criteria for probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The ileum contents of the chickens were diluted in peptone water (1/1), plated on MRS medium and then incubated in a modified atmosphere (5% CO 2 /95% air) at 37°C for 48 h. The purified isolates were stored deep-frozen with glycerol 15% (v/v) and skim milk 5% (v/v) at 80°C for future studies. Moreover, 10 strains of LAB probiotics bacteria, including L. reuteri (M20) L. crispatus (M21, OR7, OR9, OR10), L. salivarius (ES7), L. oris (M4, M9), L. vaginalis (M2) and L. agilis (M17) previously isolated from healthy Iranian household native chickens ( 22 , 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…The isolated Lactobacillus bacteria were screened based on tolerance to acidic pH (at MRS medium adjusted at pH 2.5 and 5), tolerance to bile salt (MRS broth containing 0.3% oxgall; Ox-Bile LP0055; Oxoid), salt tolerance (MRS broth containing 6 and 10% (w/v) NaCl), temperature tolerance (15 and 45°C), antibiotic resistance assay and antagonistic activity based on method previously described by Aazami et al ( 21 , 22 ). Additionally, aggregation test was done according to the protocol of Reniero et al (1992) in which strain was considered as aggregation positive when clearly visible sediment consist of aggregated cells were formed to the bottom of tubes within 2 h (lower aggregation time indicates greater aggregation of that strain) ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the conventional treatment of infections is based on antibiotic therapy. However, the increase of multidrug-resistant pathogens, due to the overuse of antibiotics in human medicine and its intensive use in the animal industry, causes increased concerns about the efficacy of this treatment, which requires the search for new alternatives to antibiotics (Abdul Hafeez et al 2019;Geeta et al 2021;Aazami et al 2016) In the present study we identified the species of Lactobacillus detected in honey samples from Mostaganem region in Northwest ALGERIA by the repetitive element palindromic-polymerase chain reaction (REP-PCR) and we also, evaluated their antimicrobial activity against some pathogenic bacteria responsible of bovine mastitis.…”
Section: Introductionmentioning
confidence: 99%